(untitled) (Información, cultura y sociedad, 2004)
It is proposed to distinguish among different historic types of societies, according to the form in which the information is produced, flows, is consumed, and to the way it appears, has influence on, and is thought about. The role of five conditions and characteristics (social life dynamics and changes, globalization, liberal market, technological advances, and high socio-economic level) on the occurrence and performance of the information society is emphasized. The scope and limitations of that new type of social organization are analyzed here from a humanistic point of view.